Evolution in karst massifs: Cryptic diversity among bent-toed geckos along the Truong Son Range with descriptions of three new species and one new country record from Laos - Luu, Vinh Quang; Bonkowski, Michael; Nguyen, Truong Quang; Le, Minh Duc; Schneider, Nicole; Ngo, Hanh Thi; Ziegler, Thomas (Zootaxa, 2016)
Species designated as ‘cryptic’ share a similar morphotype, and are often only clearly separable by molecular data. Cyrtodactylus, the most diverse gecko genus of the family Gekkonidae, is a prime example, because many morphologically similar taxa have only recently been identified as new species as a result of available genetic evidence. However, while cryptic diversity of Cyrtodactylus is already well documented on the Vietnamese side of the Truong Son range, only scarce data is available from central Laos. In this study, we address this issue by means of an integrative approach, which employs morphological, molecular, and ecological data to distinguish cryptic species of the Cyrtodacylus phongnhakebangensis species group primarily distributed along the northern Truong Son Range. Our analyses based on 12 selected morphological characters, a partial mitochondrial gene (COI), and five ecological parameters revealed three undescribed cryptic Cyrtodactylus species from Hin Nam No National Protected Area, which are described as Cyrtodactylus calamei sp. nov., Cyrtodactylus hinnamnoensis sp. nov., and Cyrtodactylus sommerladi sp. nov. A fourth discovered Cyrtodactylus population in Hin Nam No proved to be the first country record of C. cryptus for Laos. Our results highlight the importance of applying an integrative approach to resolving the taxonomy of complex and cryptic species groups, and the role of the Truong Son Range in maintaining the high level of biodiversity over time.